Precursors of the botanical exploration of South America. Willem Piso (1611–1678) and Georg Marcgrave (1610–1644) - Ossenbach, Carlos (2017)
The Dutch colonization of northeastern Brazil from 1630 to 1654 is described, with emphasis on the years 1636–1644, when the colony was under the administration of Johan-Maurits Prince of Nassau-Siegen (1604–1679). During his rule, the Company sent the geographer and astronomer Georg Marcgrave (1610–1644) and the physician Willem Piso (1611–1644) to Recife. Both explored northern Brazil and made rich botanical and zoological collections, which were published in Amsterdam in 1648, after Pisos’s return, under the title Historia Naturalis Brasiliae; a second edition followed in 1658. In this work Piso mentions for the first time the orchid Vanilla in its current spelling. Both Piso and Marcgrave collected and illustrated Catasetum maculatum L.C.R., whilst a third orchid species, Trigonidium acuminatum Batem., can be found in Marcgrave’s herbarium.